Synthesis of Cyclic α-Aminophosphonates through Copper Catalyzed Enamine Activation. - Han, J; Paton, R; Xu, B; Hammond, G (Georg Thieme Verlag, 2013)
A copper-catalyzed tandem cyclization triggered addition strategy that relies on electrophilic enamine activation has been used to synthesize various cyclic α-aminophosphonates derivatives in good to excellent yields. Both five and six membered rings can be generated under mild conditions with high regioselectivity. A mechanism based on copper catalyzed enamine activation is proposed.